Siedem sekretów literatury i sztuki - Hendrykowski, Marek (Przestrzenie Teorii, 2023)
This essay deals with some of the secrets that have been studied and explored for centuries by the science of literature and the sciences of art. The author searches for the logical-philosophical origins of the phenomenon of ‘mystery’, and discovers them in the sphere of the autotelic properties and anthropocultural functions of literature and art.